REVIEW KRITIS TERHADAP “THE FUTURE OF RELIGIOUS STUDIES” DAN RELEVANSINYA BAGI STUDI AGAMA DI INDONESIA - Nana Supiana; Dody S. Truna; Rifki Rosyad (Department of Islamic Community Development, Faculty of Da'wah, State Islamic University (UIN) of Sultan Maulana Hasanuddin Banten, 2025)
This article critically reviews The Future of Religious Studies, which reflects on the historical evolution and methodological transformation of religious studies from modernity to postmodernity. Using a qualitative approach through literature review, the study analyzes how the text challenges the dominance of Western rationality and promotes an interdisciplinary paradigm that integrates theology, philosophy, and the social sciences. The discussion highlights the transition from essentialism to methodological pluralism, emphasizing religion as a dynamic and contextual phenomenon. The review argues that the future of religious studies lies in its ability to remain reflective, humanistic, and socially transformative. In the Indonesian context, this perspective provides a valuable framework for developing a contextual and dialogical approach to studying religion amid pluralism, digitalization, and socio-political change.